Exploring the research opportunities for MSMEs in Indonesia: a bibliometric study - Eldodo Saeed, Abdelrahman Musa; Hamdan, Hamdino (2025)
Micro, Small, and Medium Enterprises (MSMEs) are increasingly recognised as vital components across diverse sectors. Despite the growing scholarly and professional interest in MSME research, there has been a lack of comprehensive analyses that explore current trends and future directions, particularly within the Indonesian context. Existing reviews often limit themselves to specific conceptual or contextual aspects, such as finance or marketing, and rely on traditional descriptive methods. This study addresses this limitation by performing a bibliometric analysis of 438 articles published in Scopus-indexed journals from 2013 to 2023, employing R-programming for a robust evaluation. The review presents an updated and thorough overview of MSME research, identifying significant patterns in publication performance, author contributions, organisational roles, and journal impact. It maps out the evolving trends and potential future developments in MSME research, offering valuable insights for researchers and practitioners aiming to influence the field's trajectory in Indonesia and internationally.